Neurological manifestations of acute SARS-CoV-2 infection in a reference hospital in Bahia, Brazil - Jesângeli de Sousa Dias; Maria Augusta Moreira Rebouças; Lilian Verena da Silva Carvalho; Thais Sampaio Silva; Jair Santana dos Santos; Astrid Xiomara Tatiana Otero Melendez; Carlos Brites (Brazilian Journal of Infectious Diseases)
Background: Neurologic manifestations of Coronavirus Disease-19 (COVID-19) have been associated with patients’ disease severity and outcome. This study aimed to describe the frequency and characteristics of the neurological manifestations in a group of hospitalized individuals with COVID-19 and their associations with patient outcomes. Methods: Patients aged 18 years or older admitted to a local hospital between April and June 2020 with SARS-CoV-2 detected by RT-PCR were included in this retrospective observational study. The characteristics of participants were collected from electronic medical records using a structured questionnaire. A Poisson regression model was used to examine the influence of neurological manifestations on mortality. Results: A total of 305 participants with COVID-19 were included, with 57.7 % of them presenting neurological symptoms. There were 62 (20.3 %) individuals with acute encephalopathy, with a mean age of 65.5 ± 15.9 years. In this group, higher Prevalence Ratios (PR) of comorbidities (1.6) and severe disease (3.6) were present, predisposing factors for acute encephalopathy. They were also more likely to be admitted to the intensive care unit (3.1) and to die (2.4). The median Neutrophil-Lymphocyte Ratio (NLR) was 7 (Interquartile Range [IQR: 4‒12]). Fifty-two (17 %) participants presented chemosensory dysfunction, with a mean age 53.3 ± 14 years and a lower PR of comorbidity (0.8) than those without. The severe diseases’ PR was slightly higher (1.1), but the PR of ICU admission (0.7), and deaths (0.4) was lower. The LNR was 3.8 (IQR: 2.2–7.8). Poisson regression analysis revealed that severe illness (PR = 3.13), cardiopathy (PR = 1.65), acute encephalopathy (PR = 1.49), diabetes (PR = 1.46), and neutrophil-lymphocyte ratio (PR = 1.04) were associated with death. Conversely, having chemosensory disorders (PR = 0.44) and a prolonged hospital stay (PR = 0.96) were associated with survival. Conclusion: Patients with acute encephalopathy had more severe forms of COVID-19 and higher mortality. In contrast, chemosensory dysfunction was associated with milder disease manifestations and a better prognosis.